Massive Right Ventricular Myxoma Presenting as Right Heart Failure with Systemic Congestive: A Rare Case Report - Putra, Pantes Irsa Mahendriyansa; Failasufi, Mirza; Budiarti, Anna (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Cardiac myxomas are the most common primary cardiac tumors, predominantly located in the left atrium, with only 3–4% occurring in the right ventricle. Case description: This report presents a rare case of a massive right ventricular myxoma in a 47-year-old woman, manifesting as right-sided heart failure and systemic congestion. The patient experienced progressive shortness of breath, palpitations, and fatigue over three months. Clinical examination revealed a systolic murmur, while imaging studies, including transthoracic echocardiography (TTE), identified a large mobile mass in the right ventricle obstructing the tricuspid valve. Definitive diagnosis was confirmed through histopathological analysis following successful surgical resection. Conclusion: This case underscores the diagnostic challenges posed by atypical presentations of cardiac myxomas, particularly in the right ventricle. Differentiating myxomas from other cardiac masses requires advanced imaging techniques and clinical precision. Early surgical intervention is critical for favorable outcomes. The report highlights the importance of comprehensive diagnostic approaches and timely management to address severe complications associated with ventricular myxomas.